Nationalsozialismus und Recht Zweite und Dritte Babelsberger Gespräche (Nomos Verlagsgesellschaft mbH & Co. KG, 2018)
The first volume (2014) in this series addressed the current state of research on law and injustice under National Socialism. This second volume documents the discussions held in Munich (2013) and Rostock (2015). It again takes up the themes of 'research omissions' and the relationship between 'law and morality'. Under the umbrella term of 'techniques and areas of control and domination', the subjects this book deals with are 'decrees by the Führer and the law', the 'national community' as a fighting slogan, the revision of divorce legislation, the persecution of 'Jews in the Nazi regime', the 'dictatorial state during peacetime' and the 'rule of NSDAP's Gauleiter'. Further contributions address the Catholic Church and Protestantism under National Socialism, the American university historian Edward Y. Hartshorne and international law before and after 1933.With contributions byWolfgang Benz, Uta Gerhardt, Klaus-Dieter Grunwald, Heinz Holzauer, Martin Moll, Thilo Ramm, Hubert Rottleuthner, Bernd Rüthers, Lucia Scherzberg, Matthias Schmoeckel, Christine Schoenmakers, Dieter Waibel
Keywords: Rechtsgeschichte; Legal History; Recht; Nationalsozialismus; Deutschland; Konferenzschrift -- 2013 -- München; Konferenzschrift -- 2015 -- Rostock